2019
DOI: 10.1177/0284185119871670
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic MRI of the lumbar spine at 3.0 T: feasibility and image quality comparison with conventional MRI

Abstract: Background Synthetic magnetic resonance imaging (MRI), which can generate multiple morphologic MR images as well as quantitative maps from a single sequence, is not widely used in the spine at 3.0 T. Purpose To investigate the feasibility of synthetic MRI of the lumbar spine in clinical practice at 3.0 T. Material and Methods Eighty-four patients with lumbar diseases underwent conventional T1-weighted images, T2-weighted images, short-tau inversion recovery (STIR) images, and synthetic MRI of the lumbar spine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The quantitative parameters derived from SyMRI have been used for a variety of organs or diseases 15–18,23–25 . Our study demonstrated that T1 and T2 values of lumbar marrow could predict the early treatment response in newly diagnosed MM and help to precise risk stratification of the R‐ISS II stage.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The quantitative parameters derived from SyMRI have been used for a variety of organs or diseases 15–18,23–25 . Our study demonstrated that T1 and T2 values of lumbar marrow could predict the early treatment response in newly diagnosed MM and help to precise risk stratification of the R‐ISS II stage.…”
Section: Discussionmentioning
confidence: 81%
“…[15][16][17] It has previously been proposed that these parameters may comprehensively characterize metabolic changes in BM composition caused by tumor cells proliferation in patients with hematological diseases. 18 We hypothesized that the parameters of SyMRI may reflect the overall pathological changes of infiltrated marrow in MM, and can be used to evaluate the metabolic tumor burden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…64 Feasibility studies comparing synthetic and conventionally acquired 2D sequences of the spine showed good interobserver agreement, although with greater artifacts. 65,66 To date, synthetic CT data obtained from MRI have not been used successfully with neuronavigational software and are still under investigation. 67 Thorough evaluation of synthetic MRI in spine applications may yield further time savings and expanded applications for both 2D and 3D protocols.…”
Section: Further Directionsmentioning
confidence: 99%
“…Also, quantitative values (PD, T1, and T2) can be simultaneously acquired on the synthetic MRI, which enables a significant reduction in examination time with good accuracy and reproducibility for use in clinical practice (individual patient follow-up and comparison analysis ( 9 11 ). This approach has been used in the study of multiple systemic diseases of the brain ( 12 ), knee ( 13 ), spine ( 14 ), prostate ( 15 ), breast ( 16 ), bladder ( 17 ), and nasopharynx ( 18 ).…”
Section: Introductionmentioning
confidence: 99%